Temporal characterization of biocycles of mycelium-bound composites made from bamboo and Pleurotus ostreatus for indoor usage - Gan, Jun Ken (2023)
Mycelium-bound composites (MBCs) are materials obtained by growing fungi on a ligno-cellulosic substrate which have various applications in packaging, furniture, and construction industries. MBCs are particularly interesting as they are sustainable materials that can integrate into a circular economy model. Indeed, they can be subsequently grown, used, degraded, and re-grown. Integrating in a meaningful biocycle for our society therefore demands that MBCs fulfil antagonistic qualities which are to be at the same time durable and biodegradable. In this study, we conduct experiments using MBCs made from the fungus species Pleurotus ostreatus grown on bamboo microfibers substrate. By measuring the variations of the mechanical properties with time, we provide an experimental demonstration of a biocycle for such composites for in-door applications. We found that the biocycle can be as short as 5 months and that the use of sustainable coatings is critical to increase the durability of the composites while maintaining biodegradability. Although there are many scenarios of biocycles possible, this study shows a tangible proof-of-concept example and paves the way for optimization of the duration of each phase in the biocycle depending on the intended application and resource availability.